Integrated carboxylic carbon nanotube pathways with membranes for voltage-activated humidity detection and microclimate regulation. Issue 22 (14th June 2015) - Pingitore, V.; Miriello, D.; Drioli, E.; Gugliuzza, A.
<x xml:space="preserve">Abstract</x> Synergic donor–acceptor interactions are regarded as controlling factors for combined enhanced electrical response and moisture regulation in a unique hybrid-composite microarray.